Essentials of Human Anatomy and Physiology - Marieb, Elaine Nicpon 1936-; Keller, Suzanne M. (Pearson Education, 2021)
For one-semester Anatomy & Physiology courses. Focus on the essential what, how, & why of human anatomy & physiology With the 12th Edition of Essentials of Human Anatomy & Physiology, science educator Suzanne Keller joins bestselling author Elaine Marieb in helping learners focus on the essential What, How, & Why of A&P, without getting sidetracked in unnecessary details. Thoroughly updated with dozens of new figures, photos, and current information on medical recommendations and terminology, the 12th Edition continues to set the standard for brief, accessible one-semester. The authors hallmark clear and friendly writing style has been strengthened with familiar analogies and abundant mnemonic cues that help students learn and remember concepts. Continuing to offer just the right balance of anatomy, physiology, and clinical coverage, engaging new chapter previews help learners hone in on what structures and functions they are studying, how they function, and why they are important to learn. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you will receive via email the code and instructions on how to access this product